2019
DOI: 10.1177/0883073819871854
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness Oral Theophylline, Piracetam, and Iron Treatments in Children With Simple Breath-Holding Spells

Abstract: Breath-holding spells (BHS) are common nonepileptic paroxysmal events in children. This is a retrospective study to compare the effectiveness of oral theophylline, piracetam, and iron treatments in children with simple BHS. A total of 146 children (75 girls and 71 boys) with simple BHS were included to this retrospective study. Children were divided into 4 groups: nontreated (no anemia and no treatment), oral theophylline (10 mg/kg/d as a single daily dose), piracetam (40 mg/kg/d in 2 divided doses), and eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…We observed that our sample included more girls than boys, and rates of complete remission with iron therapy were also higher in girls. Previous studies have reported a male predominance (8) or no significant sex difference (2,3,10,11). The female predominance in the present study may be due to the sample selection.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We observed that our sample included more girls than boys, and rates of complete remission with iron therapy were also higher in girls. Previous studies have reported a male predominance (8) or no significant sex difference (2,3,10,11). The female predominance in the present study may be due to the sample selection.…”
Section: Discussioncontrasting
confidence: 55%
“…Data on the genetic predisposition or family history of BHS may vary between countries. Studies from Turkey have reported similar figures (10,11).…”
Section: Discussionsupporting
confidence: 52%
“…Both the average number of seizures and no seizure rates decreased statistically significantly as the period of use increased. However, a study was recently published reporting piracetam was not efficacious (29).…”
Section: Discussionmentioning
confidence: 99%
“…If symptoms are severe, other drugs can be tried. Studies of treatment modalities are shown in Table 3 [ 73 - 84 ].…”
Section: Late Infancymentioning
confidence: 99%